Astrocyte Glutamate Uptake and Signaling as Novel Targets for Antiepileptogenic Therapy - Peterson, Allison R.; Binder, Devin K. (Frontiers in Neurology, 2020)
Astrocytes regulate and respond to extracellular glutamate levels in the central nervous system (CNS) via the Na+-dependent glutamate transporters glutamate transporter-1 (GLT-1) and glutamate aspartate transporter (GLAST) and the metabotropic glutamate receptors (mGluR) 3 and mGluR5. Both impaired astrocytic glutamate clearance and changes in metabotropic glutamate signaling could contribute to the development of epilepsy. Dysregulation of astrocytic glutamate transporters, GLT-1 and GLAST, is a common finding across patients and preclinical seizure models. Astrocytic metabotropic glutamate receptors, particularly mGluR5, have been shown to be dysregulated in both humans and animal models of temporal lobe epilepsy (TLE). In this review, we synthesize the available evidence regarding astrocytic glutamate homeostasis and astrocytic mGluRs in the development of epilepsy. Modulation of astrocyte glutamate uptake and/or mGluR activation could lead to novel glial therapeutics for epilepsy.